Case Report: Trendelenburg gait caused by retained drain fragment: a rare complication of total hip arthroplasty - Aydemir, Selahaddin; Aydin, Ozgur; Çeltik, Mustafa; Duymaz, Burak; Erduran, Mehmet (Frontiers in Surgery, 2025)
Retained drain fragments, though rare, can lead to significant complications in orthopedic surgery(1). This case report presents a 57-year-old woman who developed gluteal tendinopathy and Trendelenburg gait two years after a total hip arthroplasty (THA) due to a retained drain fragment. A less experienced surgeon encountered resistance during drain removal on the first postoperative day and applied excessive force, unknowingly leaving a fragment inside. The patient initially had no symptoms, but later presented with pain and gait disturbances. Radiographic evaluation revealed the retained drain, necessitating surgical removal and gluteus medius augmentation. The patient subsequently underwent a structured rehabilitation program. This case emphasizes the importance of careful drain management, proper postoperative evaluation, and collaborative patient-doctor decision-making to prevent such complications.